Epidemiological characterization of nursing students and the consumption of anime and manga, POLISAL UNAN MANAGUA. Nicaragua. First semester 2019 (Revista Torreón Universitario, 2023)
Objective. To epidemiologically characterize the population of nursing students before the consumption of anime, manga, and dorama, POLISAL UNAN Managua. Nicaragua, first semester 2019. Methodological Design: With 249 nursing students who participated in the study with a descriptive and cross-sectional research route, an instrument containing variables under study such as sociodemographic, consumption, risk of Hikikomori, data collection, filling, tabulation, analysis, and discussion were carried out in November 2019. Results: the predominant age was between 18 and 25 years of age in the profile of obstetrics and perinatology nursing with 97 (38.96%) students from the city of Managua, of which 83 (44.3%) are female and 17 (35.42%) male, 99 (39.76%) consume anime, manga or dorama being the largest consumers those of obstetric nursing and perinatology and of these 57 (49.91%) do so through the internet with 54 (54.5%), dedicating 1 to 2 hours from 7 to 12 midnight (MN) with 26 (26%). Both demographic and thematic gender do not know the classification and of the total population of the study, 141 (57%) are at risk of developing Hikikomori syndrome. Conclusions: The study population was between 18 and 25 years old, with obstetrics and perinatology predominating. This population came mainly from Managua and Masaya and less than half of the population consumes anime through the internet, preferring animated series at night, of all participants more than half have the threshold to be categorized as at risk of Hikikomori syndrome.
Keywords: Hikikomori syndrome; University students; Anime consumption; Mental health